Effects of acetylcholinesterase inhibitor Donepezil on cognitive function and vital sign in patients with dementia - Maria Yosita Ayu Hapsari; Fathu Thaariq Baihaqy; Muhana Fawwazy Ilyas; Pepi Budianto; Revi Gama Hatta Novika (Jurnal Kedokteran Syiah Kuala, 2023)
The prevalence of people with dementia is increasing both in Indonesia and throughout the world. Donepezil is one of the dementia therapy options that has been shown to have benefits. This study aims to determine the relationship between the administration of donepezil with cognitive function and vital signs: systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) in patients with dementia. The research was conducted at Dr. Moewardi Hospital (RSDM), Surakarta, Indonesia from September 2021 to February 2022 using a quasi-experimental design with different designs: one-group pretest-posttest design and time-series design. This study followed people with dementia who were given donepezil for 20 weeks. The patient was given donepezil 5 mg daily and scheduled for evaluation by the neurologist every 4 weeks to check vital signs. Cognitive function examination was performed with Mini-Mental State Examination (MMSE) at initial (before drug administration) and final (after 20 weeks). The analytical test included: repeated measures Anova, Friedman alternative, and paired T-test. A total of 27 patients were included in this study. There was an association between the administration of donepezil with cognitive function in patients with dementia at the RSDM (p0.004). Meanwhile, there was no significant association between the administration of donepezil and vital sign parameters (SBP, DBP, and HR).